Institutional endogeneity and third-party punishment in social dilemmas - Marcin, Isabel; Robalo, Pedro; Tausch, Franziska (Journal of economic behavior & organization, 2019)
This paper studies experimentally how the endogeneity of sanctioning institutions affects the severity of punishment in social dilemmas. We allow individuals to vote on the introduction of third-party-administered sanctions, and compare situations in which the adoption of this institution is endogenously decided via majority voting to situations in which it is exogenously imposed by the experimenter. Our experimental design precludes the self-selection and signaling effects that arise when subjects can vote on the institutional setting. We find that punishment is significantly higher when the sanctioning institution is exogenous, which can be explained by a difference in the effectiveness of punishment. Subjects respond to punishment more strongly when the sanctioning institution is endogenously chosen. As a result, a given cooperation level can be reached through milder punishment when third-party sanctions are endogenous.
Gesehen am 11.07.2019